Effect of vegetation on density thresholds of adult desert locust gregarization from survey data in Mauritania. Issue 2 (30th September 2013) - Cisse, Sory; Ghaout, Saïd; Mazih, Ahmed; Babah Ebbe, Mohamed Abdallahi Ould; Benahi, Ahmed Salem; Piou, Cyril
Abstract In the desert locust, Schistocerca gregaria (Forskål) (Orthoptera: Acrididae), the threshold density inducing the gregarization phenomenon has never been determined under natural conditions. The influence of environmental factors on this phenomenon has been studied mostly in controlled environments. Based on data collected during several years by the survey teams of the National Center for Locust Control in Mauritania, we analyzed the influence of locust density, vegetation cover, and vegetation status on the probability of observing gregarious locusts. We assumed that a probability to observe gregarious locusts of 0.5 corresponded to the density threshold of gregarization. The results showed in detail the change in the threshold of gregarization according to the cover and status of the vegetation. Low cover and dry vegetation led to a low density threshold of gregarization probably due to high probability of individuals to touch each other. Dense and green vegetation favored a high threshold of gregarization probably due to a dispersion of the individuals and a low probability of individual encounters. These findings should help the management of locusts and decision making during control operations.